"All is vanity, nothing is fair": Thackeray on heroism and money. (6th December 2020) - Kuehn, Julia
Abstract : This article analyzes what it means to be a hero or heroine in the world of William Thackeray's novel Vanity Fair . It argues that Thackeray offers a new and modern vision of heroism, one that is ordinary and canny rather than the result of a privileged birth or physical strength; one that leads the male and female protagonists of Vanity Fair from the chivalrous and brave worlds of Jane Austen and Sir Walter Scott towards the principles of On Liberty and Das Kapital . The article situates heroism, first, in the context of Thomas Carlyle's and conventional ideas of (military and male) bravery. It then analyzes Becky Sharp's path and character within the context of modern capitalism and a money‐ready society, as it reads Karl Marx's essay "The power of money in a bourgeois society" alongside Thackeray's text.